Mutations in EDA and EDAR genes in a large Mexican Hispanic cohort with hypohidrotic ectodermal dysplasia - Salas Alanís, Julio César; Wozniak, Eva; Mein, Charles A.; Duran Mckinster, Carola C.; Ocampo Candiani, Jorge; Kelsell, David P.; Hua, Rong; Garza Rodríguez, María de Lourdes; Choate, Keith A; Barrera Saldaña, Hugo Alberto (2015)
Ectodermal dysplasias (ED) encompass nearly 200 different genetic conditions identified by the lack, or dysgenesis, of at least two ectodermal derivatives, such as hair, nails, teeth, and sweat glands. Hypohidrotic/anhidrotic ED (HED) is the most frequent form of ED and it can be inherited as an X-linked (XL)-HED (MIM 305100), autosomal recessive (AR)-HED (MIM 224900), or autosomal dominant (AD)-HED (MIM 229490) condition. HED is caused by mutations in any of the three ectodisplasin pathway genes: ectodisplasin (EDA), which encodes a ligand for the second gene, the EDA receptor (ectodysplasin A-receptor, EDAR), and EDARADD, an intracellular signaling for this pathway. HED is characterized by a triad of clinical features including absent or diminished eccrine sweat glands, missing and/or malformed teeth, and thin, sparse hair. It also includes dryness of the skin, eyes, airways, and mucous membranes, as well as other ectodermal defects and, in some cases, fever, seizures, and rarely, death. XL-HED is caused by mutations in the EDA gene, located on chromosome Xq12-q13.1, which encodes a signaling molecule of the tumor necrosis factor (TNF) superfamily. AR- and AD-HED are caused by mutations in the EDAR gene, located on chromosome 2q11.q13 or the EDARAssociated Death Domain encoding gene, EDARADD, located on chromosome 1q42-q431. Several mutations in the EDA, EDAR, and EDARADD genes have been described as causing HED in different populations. The XL-HED form is the most common and is responsible for 90% of all HED cases2-6. The three forms of HED are clinically indistinguishable. To date, a comprehensive evaluation of HED in the Mexican Hispanic population has not been undertaken. In the present study, we aimed to characterize the mutations in EDA, EDAR, and EDARADD genes present in Mexican Hispanic patients with HED. Male and female patients (35 families) from different geographical regions of Mexico with features suggestive of HED were enrolled in the study (Fig. 1). Index cases and their parents were screened for missing or malformed teeth, thin or sparse hair, and nail changes; all subjects answered questions about sweating, heat intolerance, fever, seizures, and family history of siblings deceased due to unknown fever